Adaptation of a food environment typology for urban Sri Lanka - Marshall, Quinn; Hewavidana, Budni H. (International Food Policy Research Institute, 2024)
As a sub-study within the R5N evaluation, the International Food Policy Research Institute (IFPRI), University of Peradeniya, and Johns Hopkins University collected food environment data in 45 Grama Niladahari (GN) Divisions across 5 Districts of rural Sri Lanka from December 2020 to March 2024. These communities were in areas where the World Food Programme was targeting a nutrition sensitive resilience program (R5N) to smallholder farming families. The communities were in the agro ecological dry zone of Sri Lanka. The R5N program sought to increase their access to water for irrigation via creation and rehabilitation of community and household irrigation schemes, while also improving nutrition through a behavior change communication activity. In these contexts, the primary access points for food purchases are through periodic open-air markets (known as pola) and small village retail shops. Many of the communities were in relatively remote areas where the density of food vendors was low. Data collected primarily focused on food prices and food availability as a means of monitoring the cost of a healthy diet and the availability of nutritious food through monthly follow-ups. Other data collected have described market and shop characteristics—such as size, access to roads, electricity, and cold storage.